Breastmilk fatty acids in relation to sensitization – the ALADDIN birth cohort. Issue 10 (25th May 2016) - Rosenlund, H.; Fagerstedt, S.; Alm, J.; Mie, A.
Abstract: Background: Breastmilk fatty acids (FAs) have been associated with childhood allergic disease. Children of families with an anthroposophic lifestyle have a low prevalence of sensitization compared to reference groups. This study aimed to investigate whether the lower prevalence of sensitization among these children can be explained by the differences in breastmilk FA composition. Methods: The prospective birth cohort ALADDIN included 330 children from anthroposophic, partly anthroposophic and nonanthroposophic families recruited between 2004 and 2007 in Sweden. In total, 245 breastmilk samples, collected at 2 months of age, were analysed for FA composition. Allergen‐specific IgE levels against seven common allergens were measured in the blood samples at the ages of 6, 12 and 24 months. Data were analysed longitudinally using generalized estimating equations. Results: An inverse association was observed between total concentration of omega‐3 PUFA in breastmilk and sensitization in the child up to 24 months of age (highest vs lowest quartile, RRadj 0. 49, 95% CI 0.23–1.05, P for trend 0.024). No associations were observed between omega‐6 PUFAs or ruminant FAs and sensitization. Overall, we observed 56% lower risks of sensitization among the anthroposophic group compared to the nonanthroposophic group (RRadj 0.44, 95% CI 0.21–0.90). This association remained largely unchanged when breastmilk omega‐3 PUFA was included in the model. Conclusion: Our results indicate that a higher concentration of omega‐3 PUFAs in breastmilk may be associated with a reduced risk of sensitization up to 24 months of age; however, this did not explain the lower risk of sensitization among children of anthroposophic families.